Analisis Kelayakan Sistem Pentanahan pada Instalasi Listrik Gedung Menara Berdasarkan Puil 2011 - Muhammad Wildan Salama; Priyo Adi Sesotyo; Ari Endang Jayati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
Abstract: This study aims to analyze the feasibility of the grounding system and leakage current in the electrical installation of the Menara Building based on the Indonesian Electrical Installation Standard (PUIL) 2011. The research employed a descriptive quantitative method through direct field measurements using a Kyoritsu 4200 Earth Clamp Tester to measure grounding resistance and a clamp meter to measure leakage current in the distribution panels. The results showed that the grounding resistance value of the transformer grounding system was 11.17 Ω, exceeding the standard limit of ≤ 5 Ω and therefore failing to meet the required standard. Leakage current measurements indicated that several distribution panels were classified as hazardous (>30 mA), particularly those located on the 2nd, 7th, 8th, and 9th floors. In conclusion, the grounding system and several distribution panels in the Menara Building are not yet feasible according to PUIL 2011 standards and require technical improvements to enhance the safety and reliability of the electrical installation system. Keywords: Electrical Installation; Grounding; Leakage Current; PUIL 2011; Grounding System